Jamuan Bagi Non-Muslim Dengan Daging Kurban Perspektif Imam Ibnu Hajar Al-Haitami Dan Mansur Al-Buhuti - Hilman Fauzi Lubis; Sudirman Suparmin (Jayapangus Press, 2025)
The feast in the context of sacrifice is the practice of distributing and serving sacrificial meat to the community as part of a worship ritual aimed at fostering devotion and sincerity to Allah SWT. This study aims to analyze the comparative views of two great scholars, namely Imam Ibn Hajar Al-Haitami and Imam Mansur Al-Buhuti, regarding the law of distributing sacrificial meat to non-Muslims. This study is a qualitative study with a comparative normative sociological approach through a case study method. The results of the study indicate significant differences between the two views. Imam Ibn Hajar Al-Haitami argues that distributing sacrificial meat to non-Muslims is not permitted, in contrast, Imam Mansur Al-Buhuti permits giving sacrificial meat as a form of gift to non-Muslims. The comparative analysis reveals that Imam Mansur Al-Buhuti's view is more relevant to the social conditions of the Kotanopan community, which practices distributing sacrificial meat to non-Muslims as a means of strengthening inter-community relations and creating social harmony. Through this approach, the study seeks to provide new insights into the aspects of halalness, ethics, and benefits in the socio-religious practices of modern society. These findings indicate that this practice is in line with the Islamic principle of being a blessing for all of nature, while enriching the contemporary jurisprudence and providing practical guidance for Muslim communities in building inclusive social relations in a multicultural society.